2022
DOI: 10.3390/life12060847
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity of Epoxy Resin-Based Root Canal Sealers before and after Setting Procedures

Abstract: Epoxy resin-based sealers are commonly used for successful endodontic treatment. This study aimed to evaluate the cytotoxicity and genotoxicity of epoxy resin-based sealers under unset and set conditions. Three epoxy resin-based sealers were used: Adseal, AH Plus, and Dia-Proseal. To test cytotoxicity, an agar overlay test and a 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay were performed using unset and set sealers on L929 mouse fibroblasts. The genotoxicity test of the comet assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…In accordance, epoxy resin-based root canal sealers are in clinical application in dentistry for years [41]. Although some data document dose-dependent cytotoxicity and genotoxicity for epoxy resins in vitro [42], other results confirm a relative good cytocompatibility for the most products in its polymerized stage [43]. In our study, we showed that the cultivated cells from SSRT migrated into the 3D micropores of both scaffolds and found qualitative differences in SEM.…”
Section: Discussionsupporting
confidence: 64%
“…In accordance, epoxy resin-based root canal sealers are in clinical application in dentistry for years [41]. Although some data document dose-dependent cytotoxicity and genotoxicity for epoxy resins in vitro [42], other results confirm a relative good cytocompatibility for the most products in its polymerized stage [43]. In our study, we showed that the cultivated cells from SSRT migrated into the 3D micropores of both scaffolds and found qualitative differences in SEM.…”
Section: Discussionsupporting
confidence: 64%
“…AH Plus was the most widely studied in cytotoxicity assessment, thus in our study was considered as the reference sealer 19 , 33 38 . In the present study, set AH Plus exhibited above 90% of viable hGF and SC cells after both incubation periods.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many desirable features of sealants, one is biocompatibility. According to the International Organization for Standardization (ISO) 1942, the biocompatible material used in dentistry does not cause any adverse local or systemic effects when contact with vital tissue, but provides the most beneficial host response 19 , 20 . The toxicity of root canal sealers can be related directly to their components such as eugenol, bisphenol A, resin monomers; substances that are released during the setting reaction (e.g., formaldehyde) or after due to their solubility (e.g., calcium hydroxide).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the polymerization reaction of AH Plus is associated with a minor release of formaldehyde [ 36 ], which might explain why AH-Plus has been shown to be cytotoxic when freshly mixed but not when set [ 37 , 38 ]. Additionally, another study reported that ADSeal was more biocompatible than AH Plus in an MTT assay on L929 mouse fibroblasts, regardless of being set or unset [ 39 ].…”
Section: Discussionmentioning
confidence: 99%